Painting as Event: Performance and gesture in late Turner - Hélène Ibata (Interfaces)
In the last decades of his long career, J.M.W. Turner became increasingly prone to display his work on exhibition canvases, making the most of the varnishing days of the Royal Academy of Arts and British Institution to finish his paintings in public. These performative displays may be connected to the increasingly gestural nature of his production, to his quest for a form of adequation between his own emotional involvement in the process of painting and the dynamic motions of nature, but also to his new awareness of the process of pictorial creation as a lived or kinaesthetic experience in which vision and movement are fused. While romantic theories of expression may shed light on such an evolution, this article argues that Turner’s work seems to articulate a number of issues raised by phenomenological accounts of pictorial creation. According to Maurice Merleau-Ponty and Henri Maldiney in particular, the act of painting is driven by the artist’s lived experience and by the urge to show the world is as it is perceived and painted by the moving and gesturing subject, rather than simply as an object of detached vision. These analyses may shed light on Turner’s tendency, in his later production especially, to make his gestures immanent to the production of the pictorial space.